Breaking barriers to low-carbon development in Indonesia: deployment of renewable energy. Issue 4 (April 2022) - Sambodo, Maxensius Tri; Yuliana, Chitra Indah; Hidayat, Syarif; Novandra, Rio; Handoyo, Felix Wisnu; Farandy, Alan Ray; Inayah, Ika; Yuniarti, Putri Irma
Abstract: The Indonesian government is incorporating Low-Carbon Development (LCD) into its National Medium-Term Development Plan 2020–2024. In the future, the energy sector will become the largest carbon emitter unless the government commits to dissolving barriers to renewable energy expansion. Literature studies indicate four barriers to LDC namely socio-cultural, economic, technology, and governance. This research aims to examine the barriers that hinder the implementation of LCD in Indonesia and to analyze which barriers are most significant. This study uses mixed methods. Qualitative and quantitative data were generated during fieldwork in DKI Jakarta, Bali, West Nusa Tenggara, and Bangka Belitung provinces. The Partial Least Square – Structural Equation Modeling (PLS-SEM) approach was used to measure the direction and strength of the relationship. The qualitative approach is useful for further deepening the provincial context that was not captured from the previous approach. This study indicates that among those four barriers, technological and governance barriers have negative significant and direct effects on LCD, and governance needs to be treated as the most critical barrier. This study emphasizes the importance of collaboration between central and local governments in implementing LCD. Shared vision, equal responsibilities, commensurate governance roles, development of fiscal instruments, can improve the coherence and continuity of renewable energy development programs and activities. Abstract : Low-carbon development; Renewable energy; Socio-culture; Economic; Technology; Governance.